IMPLEMENTATION OF REACT STRATEGY TO DEVELOP STUDENTS ABILITY IN WRITING RECOUNT TEXT SELF EXPERIENCES AT JUNIOR HIGH SCHOOL - Dini Anggraeni; Muhammad Andriana Gaffar; Riki Ruswandi (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This study purpose to (1) to find out the learning process activity in improving the ability to write Recount Text for grade VIII students of SMPN 53 Bandung using the react strategy. (2) To find out the improvement in the ability to write Recount Text Self-Experiences for grade VIII students of SMPN 53 Bandung in writing recount text self -experiences using the react strategy. This type of research is descriptive research using a qualitative approach. Participants in the study were class VIII F SMPN 53 Bandung, totaling 33 students. This research was conducted in two cycles and data collection techniques used were Observation, Interviews and Field notes. The results of the data analysis show that the react strategy can be used to improve students' ability to write Recount Text Self-Experiences, this can be seen from the results of the achievement of the 1 and 2 cycle value, students give a very good response regarding the use of the react strategy. In addition, it also encourages students to actively follow the learning process and this react strategy to create a pleasant learning atmosphere. This strategy must be used continuously for better learning outcomes, especially in learning to write Recount Text of Self-Experiences